2011
DOI: 10.3892/or.2011.1357
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratins negatively regulate the invasive potential of lung cancer cell lines

Abstract: Abstract. Lung cancer cells express several cytokeratins (CKs) that are subdivided into type I (CK9-23) and type II (CK1-8) subclasses. The functions of CKs in lung cancer cells have not been fully elucidated. The purpose of this study was to investigate the role of CKs in the invasion of lung cancer cells. We investigated the expression levels of CK7, 8, 18 and 19 in 12 non-small cell lung cancer (NSCLC) and seven SCLC cell lines by quantitative immunoblotting. The expression levels of these four CKs were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In a similar way, stable silencing of vimentin in squamous carcinoma cells resulted in re-emergence of keratins and a concomitant reduction in cell invasiveness and tumorigenic potential (57). Conversely, suppression of both K8/18 in non-small cell lung cancer cell lines increased their invasiveness (58). In the present study, we have demonstrated that K8/18 constitutes a signaling platform capable of moderating invasion and cell death in tumor cells.…”
Section: Discussionmentioning
confidence: 58%
“…In a similar way, stable silencing of vimentin in squamous carcinoma cells resulted in re-emergence of keratins and a concomitant reduction in cell invasiveness and tumorigenic potential (57). Conversely, suppression of both K8/18 in non-small cell lung cancer cell lines increased their invasiveness (58). In the present study, we have demonstrated that K8/18 constitutes a signaling platform capable of moderating invasion and cell death in tumor cells.…”
Section: Discussionmentioning
confidence: 58%
“…Keratin expression in SCLC is weaker than in other lung cancer types, and the lack of its expression does not exclude the diagnosis of SCLC. The pathological data are corroborated by in vitro studies, which had shown that the levels of keratins expressed in SCLC cell lines were significantly lower than in the NSCLC lines (Kanaji et al, 2011). Among seven SCLC cell lines tested, only three (H69, H209 and Lu134) displayed K8 expression, and H209 were additionally characterized by K18 and K19 expression.…”
Section: Discussionmentioning
confidence: 54%
“…Despite their epithelial origin, some SCLCs are keratin-negative (Righi et al, 2017), which may sometimes cause clinically relevant diagnostic errors. The expression of keratins in SCLC is significantly lower than in the large cell neuroendocrine carcinoma (Nagashio et al, 2010) and nonsmall cell carcinoma (NSCLC) (Nobuhiro Kanaji et al, 2011), and the prognostic role of this feature in SCLC has not been extensively studied. AE1/AE3 is the most widely used antibody cocktail to detect cytokeratin expression.…”
Section: Introductionmentioning
confidence: 99%
“…Dying and stressed cells, as identified by the yellow cluster, exhibited extensive mitochondrial gene contamination and were removed from the subsequent analyses ( Fig CK7 and CK8 are highly expressed epithelial markers in NSCLC and are commonly used in cytopathological analysis of LUAD tumors (26,27). Reduced CK expression in cancer cells is often associated with loss of epithelial signatures and EMT processes (21).…”
Section: Reduced Ck Expression In Cancer Cells Is Often Associated Wimentioning
confidence: 99%